If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + -1x) + 3x = 2(3 + -1x) + 4 (2 * 3 + -1x * 3) + 3x = 2(3 + -1x) + 4 (6 + -3x) + 3x = 2(3 + -1x) + 4 Combine like terms: -3x + 3x = 0 6 + 0 = 2(3 + -1x) + 4 6 = 2(3 + -1x) + 4 6 = (3 * 2 + -1x * 2) + 4 6 = (6 + -2x) + 4 Reorder the terms: 6 = 6 + 4 + -2x Combine like terms: 6 + 4 = 10 6 = 10 + -2x Solving 6 = 10 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 6 + 2x = 10 + -2x + 2x Combine like terms: -2x + 2x = 0 6 + 2x = 10 + 0 6 + 2x = 10 Add '-6' to each side of the equation. 6 + -6 + 2x = 10 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 10 + -6 2x = 10 + -6 Combine like terms: 10 + -6 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 4-5(x-1)+3x=2x-3(2x-3) | | 2x-3(x-5)=4-2(x+4) | | 5-7x=2-9x | | 36x^3-72x^2+11x=0 | | 5y-3+y+33=6y+30-2y | | 2x+4=7x-6 | | 2m-48=6m | | 3x-7=5x+15 | | 17x^2-51x-170=0 | | 5h+6=12-h | | h=-16t^2+32t+5168 | | 4+4*5=35 | | 4b+3(b-2)=15 | | 2(4c-7)=8(c-3) | | 4ab+1-2a-2b=0 | | 0=9x^2-81 | | 22x^2-66x-616=0 | | 0=36x^2-84x+49 | | h(t)=-26t^2-32t+5 | | 64-z^6=0 | | -27=-4r-(-17) | | 14x+x=15 | | 3x^2y^4-81x^2y=0 | | 0.3(2x+7)=1.8 | | 0=-4x^2-4x-1 | | P^3q-pq=0 | | 0=3x^2-7x+4 | | 0=4x^2+4x-15 | | 0=36x^2-16 | | x^2+5=8x+14 | | 10x-4=10x+2 | | 5y-3=7+4(1y-2) |